2021
DOI: 10.1021/acsami.0c18684
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Substitution Steering Reaction Kinetics Acceleration for Ni3N Nanosheets Endows Exceptionally Energy-Saving Hydrogen Evolution Coupled with Hydrazine Oxidation

Abstract: Designing highly active transition-metal-based electrocatalysts for energysaving electrochemical hydrogen evolution coupled with hydrazine oxidation possesses more economic prospects. However, the lack of bifunctional electrocatalysts and the absence of intrinsic structure−property relationship research consisting of adsorption configurations and dehydrogenation behavior of N 2 H 4 molecules still hinder the development. Now, a V-doped Ni 3 N nanosheet self-supported on Ni foam (V-Ni 3 N NS) is reported, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…For N 2 H 4 adsorbed onto the different surfaces, the amount of electron transferred from N 2 H 4 to the RuP surface is 0.04|e| more than that on the Ru 2 P surface, suggesting a stronger interaction between *N 2 H 4 and RuP surface, thus accelerating the subsequent dehydrogenation reaction process. [ 19b,23 ] As for the desorption of N 2 molecule, more charges transfer from the Ru 2 P surface layer to the N 2 ‐intermediate, resulting in the relative instability of *N 2 , which is consistent with the free energy calculation result of the final step. Therefore, the theory and experiment elucidate that the RuP nanocatalysts show superior intrinsic electrocatalytic activity for both HER and HzOR, which would simultaneously realize the optimized hydrogen adsorption and dehydrogenation process.…”
Section: Resultssupporting
confidence: 80%
“…For N 2 H 4 adsorbed onto the different surfaces, the amount of electron transferred from N 2 H 4 to the RuP surface is 0.04|e| more than that on the Ru 2 P surface, suggesting a stronger interaction between *N 2 H 4 and RuP surface, thus accelerating the subsequent dehydrogenation reaction process. [ 19b,23 ] As for the desorption of N 2 molecule, more charges transfer from the Ru 2 P surface layer to the N 2 ‐intermediate, resulting in the relative instability of *N 2 , which is consistent with the free energy calculation result of the final step. Therefore, the theory and experiment elucidate that the RuP nanocatalysts show superior intrinsic electrocatalytic activity for both HER and HzOR, which would simultaneously realize the optimized hydrogen adsorption and dehydrogenation process.…”
Section: Resultssupporting
confidence: 80%
“…14,15 To improve the intrinsic activity of the individual active sites, conducting rational modulation on the electronic structures by means of elemental doping and material hybridization is widely used and highly effective. [16][17][18] For instance, the Zhang group demonstrated that W/P co-doping in Co 3 N could effectively reduce the potential determining step like the dehydrogenation of NHNH* to NHN*, thereby leading to more facile reaction kinetics for HzOR. 19 In addition, the NiCo/MoNi 4 interfaces on amorphous MoO x could also facilitate the HzOR process, leading to highly efficient and durable performance on hydrazine-assisted hydrogen production.…”
mentioning
confidence: 99%
“…Experiments together with DFT calculations reveal that proper dopants can optimize the electronic structure of host materials and thereby facilitating H* adsorption/desorption during the HER and dehydrogenation kinetics during the HzOR, which is desirable in hydrazine-assisted HWE. [189,190] Moreover, interfacial engineering is a powerful strategy as well to modify adsorption of intermediates and boost electron/mass transportation during the HzOR. [191,192] Therefore, Mai and co-authors fabricated a porous electrode consisting of copper-nickel nitride (Cu 1 Ni 2 -N) nanosheets with rich interfaces supported on carbon fiber cloth via a thermal ammonolysis process of CuNi-LDH.…”
Section: Hydrazinementioning
confidence: 99%